Microcontroller memory capability assessment and variant selection for reducing the cost of mechatronics. (1st January 2012) - Quigley, C.; Jones, R.P.; McMurran, R.; Faithfull, P.
The Local Interconnect Network is used to connect electronic control units and mechatronic devices together in modern vehicles resulting in the reduction of the amount of required wiring. The microcontroller is usually the most significant component of a mechatronic device. The aim of the research described in this paper is to first improve the understanding of how the memory capability of the microcontroller affects its cost, and second, to ascertain how the LIN stack properties affect the ROM/RAM requirement and whether these requirements can be estimated from the coarse information that is available at the start of an automotive project.